Solve the equation cot x + tan x = 2 cosecx
Answers
Answered by
2
As
![tan \: x = \frac{1}{cot \: x} \\ tan \: x = \frac{1}{cot \: x} \\](https://tex.z-dn.net/?f=tan+%5C%3A+x+%3D+%5Cfrac%7B1%7D%7Bcot+%5C%3A+x%7D+%5C%5C+)
put this value in the equation
![cot \: x + \frac{1}{cot \: x} = 2 \: cosec \: x \\ \\ \frac{ {cot}^{2}x \: + 1 }{cot \: x} = 2cosec \: x \\ \\ cot \: x + \frac{1}{cot \: x} = 2 \: cosec \: x \\ \\ \frac{ {cot}^{2}x \: + 1 }{cot \: x} = 2cosec \: x \\ \\](https://tex.z-dn.net/?f=cot+%5C%3A+x+%2B+%5Cfrac%7B1%7D%7Bcot+%5C%3A+x%7D+%3D+2+%5C%3A+cosec+%5C%3A+x+%5C%5C+%5C%5C+%5Cfrac%7B+%7Bcot%7D%5E%7B2%7Dx+%5C%3A+%2B+1+%7D%7Bcot+%5C%3A+x%7D+%3D+2cosec+%5C%3A+x+%5C%5C+%5C%5C+)
As
![1 + {cot}^{2} x = {cosec}^{2} x\\ 1 + {cot}^{2} x = {cosec}^{2} x\\](https://tex.z-dn.net/?f=1+%2B+%7Bcot%7D%5E%7B2%7D+x+%3D+%7Bcosec%7D%5E%7B2%7D+x%5C%5C)
![\frac{ {cosec}^{2} x}{cot \: x} = 2 \: cosec \: x \\ \\ cosec \: x = 2cot \: x \\ \\ \frac{1}{sin \: x} = 2 (\frac{cos \: x}{sin \: x} ) \\ \\ 2 \: cos \: x = 1 \\ \\ cos \: x = \frac{1}{2} \\ \\ x = {cos}^{ - 1} ( \frac{1}{2} ) \\ \\ x = {cos}^{ - 1} (cos \: ( \frac{ \pi}{3} ) \\ \\ x = \frac{\pi}{3} \frac{ {cosec}^{2} x}{cot \: x} = 2 \: cosec \: x \\ \\ cosec \: x = 2cot \: x \\ \\ \frac{1}{sin \: x} = 2 (\frac{cos \: x}{sin \: x} ) \\ \\ 2 \: cos \: x = 1 \\ \\ cos \: x = \frac{1}{2} \\ \\ x = {cos}^{ - 1} ( \frac{1}{2} ) \\ \\ x = {cos}^{ - 1} (cos \: ( \frac{ \pi}{3} ) \\ \\ x = \frac{\pi}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bcosec%7D%5E%7B2%7D+x%7D%7Bcot+%5C%3A+x%7D+%3D+2+%5C%3A+cosec+%5C%3A+x+%5C%5C+%5C%5C+cosec+%5C%3A+x+%3D+2cot+%5C%3A+x+%5C%5C+%5C%5C+%5Cfrac%7B1%7D%7Bsin+%5C%3A+x%7D+%3D+2+%28%5Cfrac%7Bcos+%5C%3A+x%7D%7Bsin+%5C%3A+x%7D+%29+%5C%5C+%5C%5C+2+%5C%3A+cos+%5C%3A+x+%3D+1+%5C%5C+%5C%5C+cos+%5C%3A+x+%3D+%5Cfrac%7B1%7D%7B2%7D+%5C%5C+%5C%5C+x+%3D+%7Bcos%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B1%7D%7B2%7D+%29+%5C%5C+%5C%5C+x+%3D+%7Bcos%7D%5E%7B+-+1%7D+%28cos+%5C%3A+%28+%5Cfrac%7B+%5Cpi%7D%7B3%7D+%29+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B%5Cpi%7D%7B3%7D+)
Since this belongs to principal value of cos -1 x.
put this value in the equation
As
Since this belongs to principal value of cos -1 x.
Answered by
0
Another method to do the same :)
Attachments:
![](https://hi-static.z-dn.net/files/d0b/9500122faef1bb87baba08392345b923.jpeg)
Similar questions